The Humour and Novelty of Congwayndut Puppet Group: An Overview of Performance Studies - Gendot Dekanipa; Aris Setiawan (Soshum: Jurnal Sosial dan Humaniora, 2023)
As a dynamic cultural event, the contemporary art of the Congwayndut group is always produced with a unique dramaturgy, contemporary and innovative setting. Congwayndut provides a sense of humour with an all-ages segmentation to entertain audiences. Regarding to the case, this paper attempts to examine performance studies through the use of performance studies reading schemes, social drama theory, and trickster in cultural practice. Through the "abnormality" of the Congwayndut perfomance, the research shows three findings namely the categorisation of stage attacks, subsidised cross-performances, and pure performances. This performance is executed with flexibility which indicating a novelty. Planning or the performance strategy that set in back stage can be different when it has been on the stage. The improvisation even provides the aesthetics of its puppet performance. The key aspect of humour and novelty in the Congwayndut is positioned at the role strategy of entul and trickster. This is very crucial in bringing the atmosphere of the performance to life, sowing the messages of the performance, and fostering a renewed image of contemporary puppet performance that is attractive to all levels of society.